Netosis and Inflammasomes in Large Vessel Occlusion Thrombi - Chen, Stephanie H.; Scott, Xavier O.; Ferrer Marcelo, Yoandy; Almeida, Vania W.; Blackwelder, Patricia L.; Yavagal, Dileep R.; Peterson, Eric C.; Starke, Robert M.; Dietrich, W. Dalton; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Pharmacology, 2021)
The inflammatory response appears to play a critical role in clotting in which neutrophil extracellular traps (NETs) are the major drivers of thrombosis in acute ischemic stroke (AIS). The inflammasome is an innate immune complex involved in the activation of interleukin (IL)-18 and IL-1 through caspase-1, but whether the inflammasome plays a role in NETosis in AIS remains poorly understood. Here we assessed the levels of inflammasome signaling proteins in NETs and their association with clinical and procedural outcomes of mechanical thrombectomy for AIS. Electron microscopy and immunofluorescence indicate the presence of NETs in thrombi of patients with AIS. Moreover, the inflammasome signaling proteins caspase-1 and apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) were also present in clots associated with the marker of NETosis citrullinated histone H3 (CitH3). Analysis of protein levels by a simple plex assay show that caspase-1, ASC and interleukin (IL)-1β were significantly elevated in clots when compared to plasma of AIS patients and healthy controls, while IL-18 levels were lower. Moreover, multivariate analyses show that IL-1 levels in clots contribute to the number of passes to achieve complete recanalization, and that ASC, caspase-1 and IL-18 are significant contributors to time to recanalization. Thus, inflammasome proteins are elevated in NETs present in thrombi of patients with AIS that contribute to poor outcomes following stroke.